Analysis Of Medicinal Plants On Embryo Development Of Mice (Mus Musculus L.) And White Rats (Rattus Novergicus): A Systematic Review - Mafruchati, Maslichah; Makuwira, Jonathan (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2022)
White rats are often used to assess protein quality, toxicity, carcinogenic, and pesticide content of an agricultural food product. M. Musculus mice are rodents that are very easy to breed, and easy to maintain. Embryogenesis is the process of growth and development of the embryo. The purpose of this study was to analyze medicinal plants on the embryonic development of Mice (Mus musculus L) and White Rats (Rattus Novergicus). This method uses a Systematic Review approach which is based on the Preferred Guide to Reporting Items for Systematic Review and Meta-analysis (PRISMA). Total of 700 articles were obtained which then entered the elimination stage resulting in 50 articles on medicinal plants (Mus musculus L) and White Rats (Rattus Novergicus). Based on the results of the study, it can be concluded that the identification of medicinal plants that are toxic to the embryonic development of Mice (Mus musculus L.) White Rats (Rattus Novergicus).